Uso de wetlands construídos na remoção de 17α-metiltestosterona de águas de piscicultura - Castanha, Andréa Paula Jardim (2019)
The fish farming has been highlighting in the national scene after incorporating cultivation and management techniques that improved the production and among them is the masculinization of the fingerlings realized with the administration of the hormone 17α-methyltestosterone. However, there are few preventive actions in the activity so that this effluent, containing the hormone, is released in natura in the aquatic environment. Therefore, there is the imminent need to develop adequate techniques for the treatment of the effluent that can retain the hormone. The present work treats the system montage of constructed wetlands whit subsurface flow and vertical flow for the retention of 17α-methyltestosterone hormone for this development of making of four prototypes containing as substrate the diatomaceous earth residue and filter sand, with analyzes UV-vis, pH, electrical conductivity, turbidity, BOD and COD, verifying the development of vegetable, retention of the hormone and hydrodynamics of the system. The system containing diatomaceous earth favored development of vegetable, but the sand filter compound development was inhibited by the absence of nutrients. At the monitoring of physical-chemical parameters it was found that the prototype with diatomaceous earth contained high values of electrical conductivity, promoted by the decomposition organic matter present in the residue and In the analysis of BOD and COD after the stabilization of the system, was verified the efficiency of 99.99% of removal. All parameters were within the values established by current legislation. The results were satisfactory in all respects, evidencing that the two substrates can be used and the constructed wetlands technique considered promising in the treatment of effluents containing the hormone 17α-methyltestosterone.